Foreign body removal and revascularization of teeth with periapical radiolucency: 18 Months' follow-up - Kaarunya Ravikumar; Yadav Chakravarthy; A Kumar; Mothiraj Samynathan; R Jeya Varshini (Wolters Kluwer Medknow Publications, 2021)
Revascularization of the dental pulp is an emerging regenerative endodontic approach in which a new tissue is formed inside the root canal by induction of blood clot, allowing the continuation in the development of root. In this case report, the effective management of previously fractured immature tooth with the presence of foreign body (wire) inside the canal and radiographic periapical radiolucency had been described. A 17-year-old patient with immature fractured upper left lateral incisor with radiographic evidence of foreign body (wire) inside the canal was treated with removal of wire by H file followed by revascularization protocol that used working length determination, 5.25% sodium hypochlorite irrigation, intracanal medication with calcium hydroxide, final irrigation with 17% ethylenediaminetetraacetic acid and saline, induction of apical bleeding and blood clot formation, and coronal seal with mineral trioxide aggregate. Patient was recalled at every 3 months and response checked as the tooth remained asymptomatic. At 18 months' follow-up, intraoral periapical radiography radiograph was taken to evaluate the revascularization procedure. The periapical radiolucency was healed and root closure began to appear. Increased thickness of root width was also found. Although revascularization shows clinically acceptable results, care should be taken to achieve proper disinfection of canals and regular follow-up to improve long-term efficacy and new approaches.